Análise dos polimorfismos no gene HLA DRB1 em pacientes com hepatite autoimune e suas complicações - Monique Ellen Gervásio Nunes (2017)
Autoimmune hepatitis (AIH) is a rare chronic inflammatory liver disease marked by a loss of immunological tolerance to self-antigens. Usually, this disease occurs between 10 and 30 years old, is considered rare in children. Comorbidity with autoimmune cholangitis may complicate this condition. Partially, susceptibility to AIH is determined by the presence of genes related to major histocompatibility complex II (MHC II) and most directly to human leukocyte antigen (HLA), in particular, allelic variants of DRB1. Few studies have demonstrated the predictive role of polymorphisms in HLA DRB1 in children with AIH and their implications for treatment. The purpose of this study was to describe frequencies of the polymorphisms in HLA gene with a relationship with autoimmunity in child and teenagers with autoimmune hepatitis with or without overlap syndrome, comparing both with a healthy control group. This is a prospective study of a cross-sectional cohort of including 43 individuals, 25 diagnosed with AIH type 1 and 18 with AIH type 1 overlap syndrome with autoimmune cholangitis. HLA-DRB1 locus was performed using PCR-SSP. The polymorphisms evaluated were HLA-DRB1*03, HLA-DRB1*04, HLA-DRB1*07 and HLA-DRB1*13. The mean age at the time of evaluation among participants to the control group had a mean age of 13.92 ± 4.55 years and the case group 15,86 ± 6,34. Our results demonstrated that individuals with HLA-DRB1*13 and HLA-DRB1*03 polymorphisms have an increased risk of developing. Children who have the disease with HLA-DRB1*13 presented a significantly increased to develop in the autoimmune cholangitis (OR = 3.96, p = 0.04). The HLA-DRB1*04 and HLA- DRB1*07 have not any association with the AIH and autoimmune cholangitis. This work contributed to the investigation of the main polymorphisms in the HLA-DRB1 gene responsible associated with AIH with or without cholangitis in the Brazilian population.